Life cycle assessment of laboratory-scale chitosan production: comparison of high-pressure processing-assisted and conventional methods - Bashir Bashiri; Ana Cristina De Aguiar Saldanha Pinheiro; Silvia Tappi; Pietro Rocculi; Aleksei Kaleda; Raivo Vilu (Proceedings of the Estonian Academy of Sciences)
Chitosan is in high demand due to its wide range of applications, resulting in a reliable market. Conventional chemical extraction methods of chitosan are harsh, require strong acids and bases, and produce toxic waste products. High-pressure processing (HPP)-assisted chemical extraction of chitosan has the potential to result in a higher production yield. It is crucial to evaluate the environmental performance of this method. This paper presents a comprehensive comparative analysis of chitosan production methods from an environmental perspective, focusing on HPP-assisted and conventional techniques. Employing life cycle assessment (LCA) methodologies, the study evaluates the environmental footprints of conventional and HPP-assisted chitosan production processes. Results reveal that HPP-assisted production exhibits superior environmental performance, particularly in reducing climate change impact by 64% compared to conventional methods. Sensitivity and scenario analyses confirm the robustness of findings, considering changes in electricity production regions and alternative characterization methods. Uncertainty analysis indicates moderate uncertainty levels, affirming data reliability. The study concludes that HPP-assisted chitosan production offers a more sustainable approach with lower environmental footprints across various endpoints. These findings provide valuable guidance for stakeholders in the chitosan industry to enhance sustainability practices and minimize environmental impacts.